2011
DOI: 10.1177/000348941112000903
|View full text |Cite
|
Sign up to set email alerts
|

Do Anatomic Variations of the Middle Turbinate Have an Effect on Nasal Septal Deviation or Paranasal Sinusitis?

Abstract: Anatomic variations of the middle turbinate have an effect on bony septal deviations to the contralateral side. However, middle turbinate variations and bony septal deviation are not associated with chronic sinusitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
2
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 6 publications
1
12
2
10
Order By: Relevance
“…10 In a study involving comparison of the sinus CT scans of 73 asymptotic patients with 461 symptomatic patients, middle turbinate variations and bony septal deviation were not found to be associated with disease. 11 It is possible that our findings differ from those reported in previous studies principally due to study design. We have sought to compare anatomical differences between subgroups of CRS, whereas in the studies we have reviewed, comparisons between the extent of sinonasal disease (local vs pansinusitis) and its correlation with anatomical variations were not reported.…”
Section: Discussioncontrasting
confidence: 97%
“…10 In a study involving comparison of the sinus CT scans of 73 asymptotic patients with 461 symptomatic patients, middle turbinate variations and bony septal deviation were not found to be associated with disease. 11 It is possible that our findings differ from those reported in previous studies principally due to study design. We have sought to compare anatomical differences between subgroups of CRS, whereas in the studies we have reviewed, comparisons between the extent of sinonasal disease (local vs pansinusitis) and its correlation with anatomical variations were not reported.…”
Section: Discussioncontrasting
confidence: 97%
“…In another similar study, no statistical relationship was found between SeD and sinusitis. They revealed that middle turbinate changes and SeD are not associated with chronic sinusitis [14]. …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Nouraei et al 457 and Bolger et al 99 found no relationship between anatomical variations of the MT or other structures that could affect the OMC and impact on LM score. Similarly, Cho et al 102 noted no correlation between MT variations or NSD and presence of sinus inflammation on CT scan.…”
Section: S63mentioning
confidence: 94%
“…Anatomic variations that may contribute to the pathophysiology of CRSsNP (ostensibly by narrowing sinus ostia) are generally divided into those that affect the OMC or those that affect frontal sinus drainage, although both pathways may be affected. 16,99,101,102,108,[453][454][455][456][457][458][459] Examples of OMC variations include concha bullosae, paradoxical curvature of the MT, infraorbital ethmoid (Haller) cells, and NSD. Frontal sinus drainage obstruction may be caused by Type 1-4 frontal sinus cells, supraorbital cells, suprabullar cells, frontal bullar cells, and intersinus septal cells.…”
Section: S63mentioning
confidence: 99%